Hydrothermal Synthesis of Carbon Micro-Particles and Their Electrochemical Performance as Anode Materials for Lithium Ion Batteries - Yan, Zhijun; Zhu, Gang (Asian Journal of Chemistry, 2013)
Carbon micro-particles with smooth surface and sphere shape were prepared through a facile hydrothermal method using b-cyclodextrin as carbon source. Galvanostatic charge-discharge method was used to investigate the electrochemical performance of carbon micro-particles. The results showed that carbon micro-particle anode exhibited an initial discharge capacity of 571 mAh/g and a reversible capacity above 345 mAh/g after 50 cycles. The good performance for the carbon micro-particles can be attributed to the smooth surface of the carbon spheres, which is advantageous for the formation of good and efficient passivation layers. This electrode material has promising applications in lithium ion batteries.